THE INFLUENCE OF THE VISUAL ANALYZER ON POSTURE AND BALANCE – REVIEW TYPE STUDY - Ana-Maria VUTAN; Kaven-Patrick OLARIU; Nicolae-Adrian JURJIU; Corina PANTEA (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2022)
Introduction: The posture of the body in space is influenced by information from outside and inside the human body. The eye has a dual role being both an exteroceptor and an enteroceptor. Exteroception is achieved through peripheral vision and proprioception is related to the activity of the extrinsic muscles of the eyes and the oculo-cephalo-gyrus pathways. Therefore, the visual analyzer can influence the posture through refractive disorders (myopia, hypermetropia or astigmatism) or blindness, but also through convergence disorders and heterophoria. Purpose: The present study was carried out with the aim of analyzing the influence of the visual analyzer in maintaining the correct posture of the body. Material and method: Search engines Google Scholar as well as Frontiers, BioMed and ScienceDirect databases were searched using keywords on the desired topic and 53 articles were found. After inclusion criteria were applied (studies from the last 15 years, full articles, studies using cohorts of subjects or case studies), 20 articles were chosen for analysis. Results: In the 20 articles chosen for the study, blind participants were discussed, healthy subjects whose response to different visual stimuli was analyzed or subjects with different visual impairments who were investigated to maintain balance and correct body posture in different conditions. Conclusions: After analyzing the 20 articles, we came to the conclusion that the visual analyzer influences balance and can produce changes in body posture in space. Improving the function of the visual analyzer can be achieved through specific exercises, various surgical interventions or balancing performed by specialists such as aophthalmologist doctor, physiotherapist or posturologist.